2013
DOI: 10.1590/s0100-204x2013001000010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização genética de gerações de tilápia Gift por meio de marcadores microssatélites

Abstract: O objetivo deste trabalho foi caracterizar a variabilidade genética nos parentais (G0) e em três gerações consecutivas (G1, G2 e G3) de tilápia Gift (genetically improved farmed tilapia), por meio de marcadores microssatélites. Trezentos e sessenta indivíduos, provenientes do programa de melhoramento da Universidade Estadual de Maringá, foram selecionados quanto ao ganho de peso. O total de 21 alelos foi encontrado nos cinco loci microssatélites polimórficos (G12292, UNH140; G12311, UNH159; G12312, UNH160; G12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, after eliminating these loci the He values slightly decreased. Sukmanomon et al (2012) and Rodriguez-Rodriguez et al (2013) observed linkage disequilibrium in different pairs of microsatellite loci in tilapia. However, these authors did not apply any correction to the data.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, after eliminating these loci the He values slightly decreased. Sukmanomon et al (2012) and Rodriguez-Rodriguez et al (2013) observed linkage disequilibrium in different pairs of microsatellite loci in tilapia. However, these authors did not apply any correction to the data.…”
Section: Discussionmentioning
confidence: 97%
“…Nile tilapia, Oreochromis niloticus (Linnaeus, 1758), is one of the most popular fish in global aquaculture and, therefore, has been a target species for numerous genetic improvement programs (Eknath & Hulata, 2009;Rodriguez-Rodriguez et al, 2013). As such, several strains have been developed and improved along the years.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in Brazil, some of these strains have been officially imported and produced since 1971 (Moreira et al, 2007;Massago et al, 2010). A few notable examples include: the Chitralada strain from Thailand, imported in 1996 from the Asian Institute of Technology (Khlong Luang, Pathum Thani, Thailand); the GenoMar Supreme Tilapia (GST) strain from Norway, imported in 2002 from GenoMar (Oslo, Norway); and the Genetically Improved Farmed Tilapia (GIFT) strain from Malaysia, imported in 2005 from WorldFish (Bayan Lepas, Penang, Malaysia) (Lupchinski Júnior et al, 2008;Massago et al, 2010;Rodriguez-Rodriguez et al, 2013;Dias et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Cm1D11 locus in G2 showed a loss in the 178 bp allele. This loss can be attributed to variations in the ringing regions of the primers, which is a very common situation in microsatellite markers (Rodriguez-Rodriguez et al, 2013). The mean values found for the Ho, when compared to the He, showed that there was a deficit in the number of heterozygotes in the parental generation G0 (-0.056), with an excess of heterozygotes in the first generation G1 (0.017) and a deficit of heterozygotes in the second-generation G2 (-0.061).…”
Section: Resultsmentioning
confidence: 99%
“…Because mating is aimed at the superior performance of the progeny, there is a clear concern regarding the genetic diversity of the generations that are developed by the breeding programs. Studies with improved Nile tilapia have revealed the importance of assessing genetic diversity in order to control inbreeding depression in herds and strains (Petersen et al, 2012;Rodriguez-Rodriguez et al, 2013). Recent studies have also highlighted this concern with stocks of Tambaqui breeders (Lopera- Barrero et al, 2015;Ribeiro et al, 2016;Santos, Santana, Leitão, Paula-Silva, & Almeida-Val, 2016;Aguiar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%